Museal Activity to Promote Geotourism and Geosite Protection: The Case of the National Ceramics Museum, Safi, Morocco - Mustapha El Hamidy; Ezzoura Errami; Mukhtiar Ghani (Geoconservation Research)
Museums, as significant actors in their respective areas, face the challenge of evolving beyond being mere repositories of heritage. They are increasingly expected to serve as instrumental contributors to balanced human development and overall societal well-being. This includes actively participating in cultural tourism and geotourism initiatives, which are essential components of broader efforts to enhance collective welfare. This study explores the role of museums in promoting geotourism and preserving geological heritage, using the National Ceramics Museum in Safi, Morocco (NCMSM) as an example. Experts agreed on the potential of museums to promote geotourism and protect geosites through a variety of activities, including geosite visits, educational programs, interpretive panels, geotours, awareness campaigns, souvenir offers, and interactive applications. These initiatives can effectively raise awareness, foster appreciation, and support the conservation of geosites, while also contributing to the development of sustainable geotourism practices. Statistically, amongst the listed activities at NCMSM, the pottery workshops are the most recommended activity as they appeal to people of all ages and levels. The ceramic-rich heritage at NCMSM is encouraged to take a holistic approach, ensuring a wider impact on public understanding, engagement, and preservation efforts.